2023
DOI: 10.1002/biot.202200365
|View full text |Cite
|
Sign up to set email alerts
|

Shell engineering in soft alginate‐based capsules for culturing liver spheroids

Abstract: Functional interaction between cancer cells and the surrounding microenvironment is still not sufficiently understood, which motivates the tremendous interest for the development of numerous in vitro tumor models. Diverse parameters, for example, transport of nutrients and metabolites, availability of space in the confinement, etc. make an impact on the size, shape, and metabolism of the tumoroids. We demonstrate the fluidics-based low-cost methodology to reproducibly generate the alginate and alginate-chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Increased viscosity of liquid MC core may affect the character of collective cell behavior, which is described in Figures 4 and Figure 5. In accordance with our previous results, [29] in this study we also observed large-scale cell spheroids within MCs with 0% CMC in the core and highly dispersed small cell clusters within GBs (Figure 4A). Optical and fluorescent images recorded during the first 9 d of culturing (Figure 4A; Figure S3, Supporting Information) reveal that cells aggregate faster in pristine AL MCs than in AL-CMC MCs with more viscous core or AL GBs.…”
Section: Proliferation Of Cells and Formation Of Spheroids In Mcs And...supporting
confidence: 93%
See 4 more Smart Citations
“…Increased viscosity of liquid MC core may affect the character of collective cell behavior, which is described in Figures 4 and Figure 5. In accordance with our previous results, [29] in this study we also observed large-scale cell spheroids within MCs with 0% CMC in the core and highly dispersed small cell clusters within GBs (Figure 4A). Optical and fluorescent images recorded during the first 9 d of culturing (Figure 4A; Figure S3, Supporting Information) reveal that cells aggregate faster in pristine AL MCs than in AL-CMC MCs with more viscous core or AL GBs.…”
Section: Proliferation Of Cells and Formation Of Spheroids In Mcs And...supporting
confidence: 93%
“…Before the culturing of cells in MCs, we confirmed that the capsule structure allows for efficient mass transfer of nutrients and metabolites through the shell. [29] Higher viscosity of the fluid is expected to reduce the diffusion rate of the molecules. To assess the impact of increased viscosity on the rate of nutrient exchange (e.g., glucose, molecular mass (M r ) of 180 Da and amino acids, M r = 80-210 Da) within the MCs during a specific period, we conducted a diffusion experiment using similarly sized model molecule -sodium fluorescein (FSC, M r = 376.27 Da, 5 × 10 −3 m solution), and visualized FSC permeation using a confocal microscope.…”
Section: Diffusion Of Sodium Fluorescein Into Al Mcs Al-cmc Mcs and A...mentioning
confidence: 99%
See 3 more Smart Citations